National Rural Health Mission (NRHM) in Chandigarh: A Mid Term Appraisal. - Aggarwal, Rajesh Kumar and Bansal, Sunil (2011)
The National Rural Health Mission (2005-2012) is the flagship programme of the Government of India which aims at providing accessible, affordable and quality health care to the most vulnerable and marginalized population besides strengthening public health service delivery system. Though launched in 2005, it started functioning late in most of the States and UTs, particularly the non focused ones. The present paper makes a mid-term appraisal of the NRHM programme under different components as suggested in the mission document. Besides the financial performance, the paper assesses the mid-term progress achieved in terms of physical and infrastructural facilities of different components as envisaged in the mission document. The paper also discusses the performance and implementation of different national programmes in the UT of Chandigarh. The paper suggests critical areas of intervention and has clear policy implications for future improvement of the programme and is directly relevant in the wake of preparations for the forthcoming 12th Five Year Plan.